The rapidly evolving landscape of novel targeted therapies in advanced non-small cell lung cancer. (October 2021) - Melosky, Barbara; Wheatley-Price, Paul; Juergens, Rosalyn A.; Sacher, Adrian; Leighl, Natasha B.; Tsao, Ming-Sound; Cheema, Parneet; Snow, Stephanie; Liu, Geoffrey; Card, Paul B.; Chu, Quincy
Highlights: Non-small cell lung cancer is heterogenous with many targetable driver mutations. Tyrosine kinase inhibitors, monoclonal antibodies and conjugates are promising agents. Targets include ROS1, BRAF, NTRK, MET, uncommon EGFR, RET, HER2, KRAS G12C and NRG1 . FDA approved agents include those targeting ROS1, BRAF V600E, NTRK, MET and RET. Phase III trials testing ROS1, MET, EGFR, RET, HER2 and KRAS inhibitors are ongoing. Abstract: Lung cancer is a highly heterogeneous disease often driven by well-characterized driver mutations. Although the best studied are common alterations in the epidermal growth factor receptor ( EGFR ) and anaplastic lymphoma kinase (ALK) oncogenes, rapid advances in molecular characterization has led to the development of novel therapeutics that inhibit additional oncogenic alterations in advanced NSCLC. The literature search identified 62 eligible phase I/II clinical trials or integrated analyses of assessing novel targeted agents against the following molecular alterations: ROS1 -rearranged, BRAF V600E-mutant, NTRK -rearranged, MET -altered, uncommon EGFR -mutant, RET -rearranged, HER2-positive, KRAS G12C-mutant and NRG1 -rearranged. This rapidly evolving field has produced many new targeted treatment options and promising outcomes have led to the FDA approval of seven novel agents for use in ROS1 -rearranged, BRAF V600E-mutant, NTRK -rearranged, MET exon 14 skipping-mutant or RET -rearranged advanced NSCLC. Research continues at a rapid pace, with a number of phase III trials underway to fully evaluate new promising agents under development for improving outcomes in patients with NSCLC harboring distinct molecular subtypes. This review will provide a comprehensive summary of existing data as well as a user-friendly guide on the current status of novel targeted therapy in oncogene-driven advanced NSCLC.